TECHNICAL METHODS OF PLAYING VOLLEYBALL AMONG BOYS AGED 11-12 (Scientific journal of the Fergana State University, 2023)
During the game, young volleyball players lose a lot of favorable moments, as they cannot choose the best ways to strike in the fight against an opponent. In the process of explaining and studying the game technique, the basis of the technique, the sequence of movement of individual parts of the body, methods of deep study of speed and their amplitude are important when performing various techniques. These factors are the main factor in achieving the effectiveness of a volleyball player's actions. When performing and blocking an attacking strike, it is important to control the opponent during the execution of techniques. That is why young volleyball players need to master the ability to constantly monitor the opponent's movements, right up to hitting the ball.